Seasonality of tick species collected from wild boars and deer and by flagging in 2021 in Ashikaga City, Tochigi Prefecture, Japan: Reasons for tick-bite cases predominantly caused by Amblyomma testudinarium Koch in the region - Shimada, Mizuho; Doi, Kandai; Yamauchi, Takeo; Kawabata, Hiroki; Ando, Shuji; Abe, Tatsumi; Kobayashi, Yumie; Hirose, Yoshie; Kikuchi, Hiroko; Murohisa, Toshimitsu; Shimano, Satoshi (Journal of the Acarological Society of Japan, 2024)
A survey of tick species collected from wild boars (Sus scrofa) and sika deer (Cervus nippon), captured for vermin control and by flagging, was conducted in Ashikaga City, Tochigi Prefecture, Japan, in 2021 to reveal the reasons of tick-bite cases predominantly caused by Amblyomma testudinarium in the region. The results showed that the collection of A. testudinarium per wild boar was 10 times higher than that from sika deer, with the highest in April and May, based on the number of nymphs and adults, but the number of A. testudinarium collected by flagging was overly small. For Haemaphysalis longicornis, only a few ticks were collected per wild boar in early spring, whereas in the case of sika deer, the infesting numbers increased in May, reaching a maximum in July (based on adult females), along with stable collection by flagging from spring to autumn. The above-mentioned results reveal that A. testudinarium as the dominant species causing tick-bite cases closely associated with wild boars entering residential properties in the village vicinity mountainous areas in Ashikaga City. For H. longicornis, sika deer acting as a reservoir to bring and stable collection by flagging would be the reasons for small numbers but persistent tick bite cases in this area. In addition, several types of ticks were revealed to infest wild boars and sika deer even in winter, including species mainly reported in southwestern Japan.